Medical consultations and the sharing of medical images involving spinal injury over mobile phone networks - Filip, Michal; Linzer, Petr; Šámal, Filip; Tesař, Jiří; Herzig, Roman; Školoudík, David (American journal of emergency medicine, 2012)
BACKGROUND: The transmission of medical images and other data over mobile phone networks may facilitate remote medical consultations between neurosurgeons and regional hospitals treating spinal injury patients. The aim of this study was to compare the efficacy of mobile phone consultations with standard hospital workstation consultations in spinal injury patients. METHODS: The images were exported over the Internet from surrounding local hospitals through the Picture Archiving and Communication System, in DICOM III format, to the central hospital server. The xVision browser was used to view the acquired images on a standard workstation. The data were also exported to the secured hospital Web server IIS60 and converted to JPEG format to enable remote physician access and consultation. The remote consulting physician connected to this server by mobile phone using the phone's Internet browser. A second physician, blind to the mobile phone results, evaluated the same images at a workstation in the hospital. The results of the mobile phone consultations were compared with the results from standard workstation consultations. RESULTS: There was no difference in the quality of spinal computed tomographic/magnetic resonance images viewed on the phone screen compared with on the workstation. More importantly, the final diagnoses made by mobile phone did not differ from those made by workstation consultations. A transfer to the department of neurosurgery was required after consultation in 11 patients. CONCLUSION: Mobile phone consultations for patients with spinal injuries was as effective as workstation consultations. Mobile phone consultations can increase the expertise available to regional hospitals, which are often the first responders to medical emergencies.
Keywords: mobilní telefon; Teleradiology; lidé středního věku; lidé; teleradiologie; Female; mužské pohlaví; Cell Phone; Male; poranění páteře; Middle Aged; ženské pohlaví; Spinal Injuries; Humans